2017
DOI: 10.1177/1753193417702565
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interfragmentary gap on compression force in a headless compression screw used for scaphoid fixation

Abstract: We investigated the effect of an interfragmentary gap on the final compression force using the Acutrak 2 Mini headless compression screw (length 26 mm) (Acumed, Hillsboro, OR, USA). Two blocks of solid rigid polyurethane foam in a custom jig were separated by spacers of varying thickness (1.0, 1.5, 2.0 and 2.5 mm) to simulate an interfragmentary gap. The spacers were removed before full insertion of the screw and the compression force was measured when the screw was buried 2 mm below the surface of the upper b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Similar results were found in 2 separate studies that introduced gap size as a variable. Tan et al 22 found that gaps larger than 1 mm led to significant loss of reduction achieved by Acutrak 2 screws. Roebke et al 14 attributed a variety of screw parameters-screw length, pitch differential, length of screw-to their finding that Acutrak 2 screws did not fully reduce and compress 3 mm gaps.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were found in 2 separate studies that introduced gap size as a variable. Tan et al 22 found that gaps larger than 1 mm led to significant loss of reduction achieved by Acutrak 2 screws. Roebke et al 14 attributed a variety of screw parameters-screw length, pitch differential, length of screw-to their finding that Acutrak 2 screws did not fully reduce and compress 3 mm gaps.…”
Section: Discussionmentioning
confidence: 99%
“…24,25,28,35 Furthermore, previous biomechanical studies have shown that the fixation properties of the headless screw are comparable or superior to those of the solid or cancellous screws. 15,21,35,36 The Acutrak screw and the Herbert screw are the most widely used headless screws in clinical practice. The specific design features of the Acutrak screw comprise a tapered configuration with a full thread and a variable pitch, while the Herbert screw has a double-threaded design at both ends, achieving simultaneous fixation of both fragments.…”
Section: Discussionmentioning
confidence: 99%
“…4,27 Previous cadaveric studies have shown that the plantar gap widening may induce an unfavorable biomechanical environment for fracture healing. 9,13,34,36 Lee et al 18 treated 75 cases and compared the outcomes between groups with a plantar gap <1 mm and >1 mm. They reported that the mean time to obtain a bone union was significantly shorter in the group with a plantar gap <1 mm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pitch of these threads on the head is finer than those on the leading edge thereby generating compression across the fracture line. Whilst these screws have proven to be popular in the internal fixation of intra-articular fractures, notable drawbacks included the surgical exposure required, poor compressive forces and lack of versatility of screw specifications [ 5 , 6 ]. The second generation of HCS was designed to allow greater compression [ 1 ] and cannulated to allow percutaneous fixation.…”
Section: Introductionmentioning
confidence: 99%